THE EFFECT OF COMPANY SIZE, TRANSFER PRICING, AND PROFITABILITY ON TAX AVOIDANCE (Case Study of Telecommunication Sector Companies Listed on the Indonesia Stock Exchange for the Period 2016-2021) - Tika Lidiawati (Journal of Taxation Analysis and Review, 2023)
The purpose of this study was to analyze the effect of firm size, transfer pricing and profitability on tax avoidance. The independent variables used are company size, transfer pricing, and profitability. While the dependent variable used is tax avoidance. The population in this study are telecommunications companies listed on the Indonesia Stock Exchange in the 2016-2021 period. The sampling method used was purposive sampling method with a sample of 9 companies during the observation period of 6 consecutive years so that the total sample obtained was 54 samples. This analysis method uses multiple linear regression. The results of this study indicate that firm size and transfer pricing have no significant effect on tax avoidance. While profitability has a positive effect on tax avoidance. The result of the coefficient of determination shows the number 13.2%. These results indicate the ability of the independent variable to explain the dependent variable, while the remaining 86.8% is explained by other variables.